Using Open Source Health Management Information Systems in the context of Universal Health Coverage Monitoring in Malian health facilities - Karara, Gustave; Ly, Ousmane; Verbeke, Frank; Nyssen, Marc (Journal of Health Informatics in Africa, 2017)
Background and Purpose: The Universal Health Coverage (UHC) is an important point in the 2030 agenda for Sustainable Development Goals (SDGs). In this study, the authors assess indicators allowing health services coverage monitoring in the context of UHC.Methods: The study has been conducted in 4 Malian health facilities between 2013 and 2016. The most relevant UHC indicators are calculated on the basis of patient’s administrative and health insurance data, collected via an Open Source Health Management Information System (HMIS) deployed in more than fifty sub-Saharan health facilities, OpenClinic GA.Results: The results show that the patient health services coverage (PHSC) rate is 2.4% for outpatients and 18.2% for inpatients. This rate is high in the third reference hospitals where the social health insurance AMO (Assurance Maladie Obligatoire) is more applied to patient encounters. The patient health services payment (PHSP) rate as the proportion of total health service costs is above the 25% threshold recommended by WHO and it exceeds 80% both for inpatients and outpatients. The patient out-of-pocket payment (POOP) is below the threshold of 180USD per patient per year but remains high (70USD) for inpatients in the university hospital. Conclusions: This study demonstrates the possibility to evaluate the level of UHC in sub-Saharan countries, by a methodology based on health services coverage indicators calculated by using routine data recorded in patient electronic health records at the level of health facilities.